Reactive changes in the adolescent porcine spine with disc degeneration due to endplate injury - Holm, S.; Baranto, A.; Kaigle Holm, A.; Ekström, L.; Swärd, L.; Hansson, T.; Hansson, H.-A. (Veterinary and Comparative Orthopaedics and Traumatology, 2007)
Degenerative and reactive structural alterations occurring after experimentally-induced disc degeneration were evaluated using a porcine model. A cranial perforation was made through the L4 vertebral endplate into the nucleus pulposus. Three months later, the lumbar intervertebral disc and adjacent vertebrae were dissected, fixed in formalin and further processed for histopathological analyses. The results showed that there were nucleus pulposus fragments, rather than a distinct border between the nucleus and annulus fibrosus. The central lamellae were distorted and delamination of the outer anterior layers was observed. Blood vessels emerged from the adjacent tissue, penetrated the annulus and branched into the residues of the nucleus. Nerve fibres accompanying the blood vessels could be recognized in the disc within the connective scar tissue. The epiphyseal cartilage plates in the vertebrae were hypertrophic in several areas and there was bone formation directed towards the centre of the vertebral body and the disc. Hypertrophic hyaline cartilage, newly formed bone and scar tissue filled the injury canal. A slight chronic inflammatory reaction was evident along vascular buds. The reactive changes dominated over the degenerated features in the operated disc. Physiological loading enhanced the infiltration of various tissue types characterizing immature cartilage formation. Prominent neovascularisation of the central parts of the disc is likely to be of key importance in turning the degenerative features of the remaining tissue into reactive healthy structures.
Keywords: Disc injury; osteogenesis; chondrogenesis; epiphyseal cartilage; fibrosis